Avaliação do risco cardiovascular e sua associação com marcadores inflamatórios em pacientes com esquizofrenia - Ingrid Caroline Silva Dias (2018)
Introduction: Cardiovascular diseases (CVDs) are one of the leading causes of early mortality in patients with schizophrenia. More than two-thirds of patients with schizophrenia die from CVDs compared to half the general population. The high cardiovascular mortality in this group of patients may be associated with the high prevalence of cardiovascular risk factors associated with the use of antipsychotics. However, it seems uncertain that CVDs in schizophrenia are mediated only by risk factors, and a considerable amount of evidence shows a proinflammatory profile that schizophrenia presents not only in the central nervous system (CNS) but also in the periphery. The inflammatory process may involve the cardiovascular system and the cerebrovascular system, which should be considered during the investigation of the association between inflammation and the risk of cardiovascular disease in schizophrenia. Objective: The objective of this study was to evaluate the association between cardiovascular risk and inflammatory markers in patients with schizophrenia and healthy controls. Method: Patients and controls underwent clinical and laboratory evaluation, evaluation of cardiovascular risk factors, as well as the metabolic risk profile presented by the medication used by the patients. Cardiovascular risk was measured using the Framingham Score and the levels of inflammatory mediators were evaluated by cytometric beads array (CBA) and ELISA. Results and Discussion: Our study demonstrated that the risk of developing CVDs in the next 10 years was greater in patients with schizophrenia compared to healthy controls. Our results suggest that adiponectin and sTNFR2 levels are increased in patients with schizophrenia. Binary logistic regression demonstrated that increased adiponectin levels in patients with schizophrenia were independently associated with the presence of metabolic syndrome. On the other hand, it was also observed that adiponectin levels as well as sTNFR2 levels were related to cardiovascular risk in patients with schizophrenia, suggesting that increased levels of these inflammatory mediators associated with cardiovascular risk would explain higher morbidity and mortality in patients with schizophrenia. Conclusions: Overall, this data set suggests that inflammatory mechanisms would be associated with increased cardiovascular morbidity and mortality in patients with schizophrenia.